Biochar Application Alleviated Negative Plant-Soil Feedback by Modifying Soil Microbiome - Wang, Wenpeng; Wang, Zhuhua; Yang, Kuan; Wang, Pei; Wang, Huiling; Guo, Liwei; Zhu, Shusheng; Zhu, Youyong; He, Xiahong (Frontiers in Microbiology, 2020)
Negative plant-soil feedback (NPSF) frequently cause replant failure in agricultural ecosystems, which has been restricting the sustainable development of agriculture. Biochar application has appealing effects on soil improvement and potential capacity to affect NPSF, but the process is poorly understood. Here, our study demonstrated that biochar amendment can effectively alleviate the NPSF and this biochar effect is strongly linked to soil microorganism in a sanqi (Panax notoginseng) production system. High-throughput sequencing showed that the bacterial and fungal communities were altered with biochar amendment, and bacterial community is more sensitive to biochar amendment than the fungal community. Biochar amendment significantly increased the soil bacterial diversity, but the fungal diversity was not significantly different between biochar-amended and nonamended soils. Moreover, we found that biochar amendment significantly increased the soil pH, electrical conductivity, organic matter, available phosphorus, available potassium, and C/N ratio. The correlation analysis showed that these increased soil chemical variables have a significantly positive correlation with the bacterial diversity. Further analysis of the soil microbial composition demonstrated that biochar soil amendment enriched the beneficial bacterium Bacillus and Lysobacter but suppressed pathogens Fusarium and Ilyonectria. In addition, we verified that biochar had no direct effect on the pathogen Fusarium solani, but can directly enrich biocontrol bacterium Bacillus subtilis. In short, biochar application can mitigate NPSF is mostly due to the fact that biochar soil amendment modified the soil microbiome, especially inhibited pathogens by enriching beneficial bacterium with antagonistic activity against pathogen.